2014
DOI: 10.1007/s12039-014-0642-8
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide oxidation using Zn–Cu–Ti hydrotalcite-derived catalysts

Abstract: Multioxide catalysts of zinc, copper and titanium with different ratios obtained from layered double hydroxide (LDH) precursors were used in the oxidation of carbon monoxide. The catalysts were characterized by energy-dispersive X-ray spectrometry, X-ray diffraction, thermal analyses (TG, DTG and DTA) and scanning electron microscopy. X-ray diffraction showed different phases of double hydroxide structures. On increasing the percentage of zinc, hydrotalcite structure became the main phase in these samples. SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Recently, Liu et al (2013Liu et al ( , 2014 observed the CH 4 oxidation by utilizing Co x Mg 6-x Mn 2 LDO as a catalyst. The maximum conversion was limited to 90% < 495°C over Co 4.5 Mg 1.5 Mn 2 LDO (Saber and Zaki 2014). Literature at a sight for CO and CH 4 oxidation over hydrotalcite catalyst is presented in Table 8.…”
Section: Non-noble Metal Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Liu et al (2013Liu et al ( , 2014 observed the CH 4 oxidation by utilizing Co x Mg 6-x Mn 2 LDO as a catalyst. The maximum conversion was limited to 90% < 495°C over Co 4.5 Mg 1.5 Mn 2 LDO (Saber and Zaki 2014). Literature at a sight for CO and CH 4 oxidation over hydrotalcite catalyst is presented in Table 8.…”
Section: Non-noble Metal Catalystsmentioning
confidence: 99%
“…Thus, it is vital to investigate an appropriate catalyst which can oxidize CH 4 along with CO at within the range of 150–450 °C. In literature, many catalysts such as platinum group metal (PGM) catalysts (Gelin et al 2003 ; Mahara et al 2017 ; Zhang et al 2014 ; Zorn et al 2010 ), perovskite (Alifanti et al 2007 ; Ciambelli et al 2001 ; Forni and Rossetti 2002 ; Kucharczyk 2015 ; Liu et al 2013 ; Najjar et al 2011 ; Wang et al 2012 ), hydrotalcite (Cheng et al 2008 ; Genty et al 2015 ; Jiang et al 2010 ; Liu et al 2014 ; Martínez-Lozano et al 2007 ; Mokhtar et al 2010 ; Saber and Zaki 2014 ; Takehira et al 2004 ), mixed metal oxides (Biabani-Ravandi and Rezaei 2012 ; Dongsheng et al 2010 ; Heo et al 2014 ; Li et al 2009 ; Trivedi and Prasad 2016 ), and spinel (Cunningham et al 1994 ; Jansson 2000 ; Tang et al 2009 ; Tao et al 2015 ; Trivedi and Prasad 2017b ; Trivedi and Prasad 2018 ) is available for individual CO and CH 4 oxidation. The PGM catalysts are highly active for oxidation, but their application is limited due to high cost, rare availability, sensitive to poisons, and sintering at high temperatures.…”
Section: Abatement Technologies Of Co and Ch 4 Emimentioning
confidence: 99%
See 1 more Smart Citation
“…A n− is an interlayer anion. Among the most studied advanced functional structures, LDHs have been used in the fields of environmental protection, catalysis, materials science, energy and biology in recent years [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The layered double hydrotalcite and hydroxide compounds have been synthesized and studied to photodegrade rhodamine-B in water, such as Cu-Ti-hydrotanxit [5]; Zn/Ti-LDH and Ag/LDH [6]. Materials like hydrotalcite and layered double hydroxide have also been synthesized for the fields of organic catalysis, petrochemical such as MgCuAl-used to selectively oxidize styrene [7], Mg-Al [8] for green hydrocarbon synthesis through decarboxylation process, Zn-Cu-Ti [9] for oxidation reaction CO, Cu-Al catalyst for alkylation reaction indole using benzaldehyde agent [10], etc. The general characterizations of hydrotalcites, modified hydrotalcites or layered double hydroxides are synthesized from salts of valence metal II and III or II and IV, ensured their molar ratios within the optimal limits (M 2+ : M' 3+ = 2: 1 or 3: 1 or 4: 1; M 2+ : M' 4+ = 5: 1 or 5: 2 ratio), at high pH from 9.0 -10.0.…”
Section: Introductionmentioning
confidence: 99%